Far from the tree : parents, children and the search for identity - Solomon, Andrew, 1963- (New York : Scribner, 2012)
In this book the author tells the stories of parents who not only learn to deal with their exceptional children but also find profound meaning in doing so. His proposition is that diversity is what unites us all. He writes about families coping with deafness, dwarfism, Down syndrome, autism, schizophrenia, multiple severe disabilities, with children who are prodigies, who are conceived in rape, who become criminals, who are transgender. While each of these characteristics is potentially isolating, the experience of difference within families is universal, as are the triumphs of love he documents in every chapter. All parenting turns on a crucial question: to what extent parents should accept their children for who they are, and to what extent they should help them become their best selves. Drawing on 40,000 pages of interview transcripts with more than three hundred families, the author mines the eloquence of ordinary people facing extreme challenges. Whether considering prenatal screening for genetic disorders, cochlear implants for the deaf, or gender reassignment surgery for transgender people, he narrates a universal struggle toward compassion. Many families grow closer through caring for a challenging child; most discover supportive communities of others similarly affected; some are inspired to become advocates and activists, celebrating the very conditions they once feared. Woven into their courageous and affirming stories is the author's journey to accepting his own identity, which culminated in his midlife decision, influenced by this research, to become a parent. In this book he explores themes of generosity, acceptance, and tolerance, all rooted in the insight that love can transcend every prejudice; and expands our definition of what it is to be human.
Son -- Deaf -- Dwarfs -- Down syndrome -- Autism -- Schizophrenia -- Disability -- Prodigies -- Rape -- Crime -- Transgender -- Father.
Includes bibliographical references (pages 831-906) and index.
National Book Critics Circle Award for Nonfiction, 2012.
Keywords: Children with disabilities -- United States -- Psychology; Exceptional children -- United States -- Psychology; Parents of children with disabilities -- United States; Parents of exceptional children -- United States; Identity (Psychology) -- United States; Parent and child -- United States -- Psychological aspects; Disabled Children -- psychology; Child, Exceptional -- psychology; Social Identification; Parents -- psychology; Parent-Child Relations; Children with disabilities -- Psychology; Exceptional children -- Psychology; Identity (Psychology); Parent and child -- Psychological aspects; Parents of children with disabilities; Parents of exceptional children; United States